Makna Hanabi Taikai Dalam Kehidupan Bagi Masyarakat Jepang - Nafis, Daffa Aulia Adzkaar; Furisari, Pipiet (KIRYOKU, 2026)
Hanabi taikai is a festival held annually in Japan during the summer. Initially, hanabi taikai was used as a means of praying for people who died due to famine caused by crop failure and cholera, but its role has shifted to visual entertainment, although hanabi is not just visual entertainment it also holds other meanings from a philosophical and social perspective. The purpose of this research is to explore the meaning contained in hanabi taikai from philosophical and social perspectives. This research uses a qualitative method with semi-structured interviews, field observations, and document studies as data collection techniques. Data was obtained from interview results, personal documentation, YouTube videos, and TikTok videos. The results of this study indicate that from a philosophical perspective, hanabi has meaning as a temporary beauty and a beauty that can be enjoyed simply. From a social perspective, hanabi has meaning as a means to strengthen togetherness and social harmony. Hanabi reminds us of transience, simplicity, and the importance of social harmony in daily life.